CORRELATION BETWEEN VITAMIN D LEVELS AND PEDIATRIC ANTHROPOMETRY STATUS IN NEONATES - Sari, Tri Elina; Muslimin, Muslimin; Radityo, Adhie Nur; Pratiwi, Rina (Medica Hospitalia : Journal of Clinical Medicine, 2022)
Background: Problems of vitamin D deficiency is now starting to become a concern in the world because 1 million people worldwide have vitamin D deficiency and nearly 50% have vitamin D insufficiency. Vitamin D deficiency is more common in neonates which can increase the risk of low birth weight and also effect on baby length, head circumference. Aim: Understanding the correlation between vitamin D levels and anthropometric status in neonates.Method: This study used an observational analytic study with a cross sectional approach. The research sample was neonates at term. The data from questionnaires and direct anthropometric measurements on neonates who came to delivery room and pediatric polyclinic of the Diponegoro National Hospital, Semarang and Dr. Kariadi General Hospital, Semarang. The data normality test used the Saphiro-Wilk test. Correlation test between vitamin D levels and anthropometric status using the Pearson test, and test levels of vitamin D with nutritional status (WHZ, WAZ, HAZ) using the Spearman test.Results: Median (min-max) neonatal vitamin D levels were 12.12 (6.09 - 19.52). There was no significant correlation between vitamin D levels and neonatal age, neonatal anthropometric status, maternal sun exposure and neonatal diet type. This is influenced by several other factors that are consistent with the theory such as neonatal nutrition, genetics, time and length of sun exposure, poor dietary intake.Conclusion: There was no significant correlation between vitamin D levels and weight, body length, height, nutritional status of WHZ, WAZ, HAZ in neonates.